Islamic Education Institution Programs That Address the Psychosocial Crises of Stude - Suhendri, Suhendri (KnE Social Sciences, 2022)
Islamic education institutions must have programs that can answer the psychosocial crises of students. In such institutions, these programs are arranged based on Islamic paradigms and values. Furthermore, these programs are operationally supported by the availability and capacity of teachers, the facilities and infrastructure, education funding, curriculum structure, learning strategies, educational supervision, counselling guidance, and family or community support. The purpose of this study was to investigate the programs of Islamic education institutions in overcoming the psychosocial crises of students. The author conducted a literature review. The results indicated that the main strength of Islamic education institutions in implementing programs to overcome the psychosocial crises of students is a comprehensive understanding of the psychological growth and development of students from the perspective of Islamic paradigms and values. Besides, this program must be supported by teachers who are skilled in implementing counselling guidance, with simultaneous supervision of educational institutions, and parental or family support. The programs used in addressing the psychosocial crises of students in Islamic educational institutions focus on good advice (mau’izhah hasanah), exemplary behavior (uswatun hasanah), practice to do one’s best (ihsan), do good earlier (fastabiqul khairat), help each other in doing good (ta’awun), sholat and du‘a. Based on the results of this study, it can be concluded that Islamic education institutions that have programs that answer the psychosocial problems of students will continue to exist and succeed in preparing tough generations in the future, especially in crises. Keywords: Islamic education institutions, psychosocial crisis, students